Asociación entre polimorfismos en los genes PNPLA3 y TM6SF2 y presencia de fibrosis en pacientes con infección crónica por virus hepatitis C - Urzúa M., Álvaro; Brahm B., Javier; Miranda B., Julio; Carreño T., Laura; Venegas S., Mauricio (Revista Hospital Clínico Universidad de Chile, 2015)
Hepatitis C virus (HCV) is a globally prevalent pathogen and a leading cause of death and morbidity. The most recent estimates of disease burden show an increase in seroprevalence over the last 15 years to 2.8%, equating to >185 million infections worldwide. Persistent hepatitis C infection is associated with the development of liver cirrhosis, hepatocellular cancer, liver failure and death. The magnitude of disease progression in chronic infection varies significantly among individuals. Several factors have been recognized as being associated with the progression of HCV-related liver fibrosis and with clinical outcomes. As liver fibrosis progression remains variable between individuals with similar environmental or virological risks, host genetic predispositions have been suggested as another critical determinant. The single nucleotide polymorphisms in Patatin-like phospholipase domain-containing 3 (PNPLA3) and Transmembrane 6 Superfamily Member 2 (TM6SF2) genes are genetic determinants of nonalcoholic fatty liver disease, in terms of inflammation and fibrosis. The possible action of the PNPLA3 and TM6SF2 polymorphisms on fibrosis development in chronic hepatis C is being studied, with controversial results.